1998
DOI: 10.1038/sj.cdd.4400322
|View full text |Cite
|
Sign up to set email alerts
|

Egr-1 inhibits apoptosis during the UV response: correlation of cell survival with Egr-1 phosphorylation

Abstract: UV irradiation of normal or immortalized cells induces a rapid increase in the expression of several transcription factors and is thought to serve a protective function. The human fibrosarcoma cell line, HT1080 clone H4, expresses almost undetectable levels of Egr-1 and does not respond to UV-C irradiation by the induction of Egr-1. The H4 cells are hypersensitive to UV which induces apoptosis and reduces clonogenicity. The introduction of exogenous Egr-1 into H4 (H4E9 and H4E4 cell-lines) confers protection f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
64
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 32 publications
8
64
0
Order By: Relevance
“…The role of phosphorylation of Egr-1 remains controversial (Cao et al, 1993;Jain et al, 1996;Huang et al, 1998;Kamimura et al, 2004). We recently observed that curcumin reduced the level of phosphorylation of Egr-1, which was mimicked by a specific MEK inhibitor (data not shown here).…”
Section: Discussionmentioning
confidence: 98%
“…The role of phosphorylation of Egr-1 remains controversial (Cao et al, 1993;Jain et al, 1996;Huang et al, 1998;Kamimura et al, 2004). We recently observed that curcumin reduced the level of phosphorylation of Egr-1, which was mimicked by a specific MEK inhibitor (data not shown here).…”
Section: Discussionmentioning
confidence: 98%
“…We have also described a series of stable transfected Egr1 clones (19). We used the clone with the maximum expression of Egr1, termed E9, to isolate and identify in vivo Egr1 target genes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, EGR-1 is a nuclear phosphoprotein (59), but the biological significance of this modification is unknown. Some reports suggest that the phosphorylated forms of EGR-1 are bound to DNA more efficiently than the non-phosphorylated forms (60).…”
Section: Discussionmentioning
confidence: 99%